[College Union second floor interior] - P. K. Phillips::::::photographer::: (1970)
The second floor, with a more spacious layout than the first floor, is more populated, with students sitting on couches as well as standing and chatting. From the large windows, sunlight fills the second floor and illuminates the College Union.